Seeley's Essentials of Anatomy & Physiology - Cinnamon L. VanPutte; Jennifer L. Regan; Andrew F. Russo (New York, New York : McGrawHill Education, 2019)
Seeley$1 (Bs Essentials of A&P provide high-quality photographs paired with brilliantly rendered illustrations help students visualize, understand, and appreciate the wonders of human anatomy. The text incorporates student-friendly Learning Strategies, Clinical View boxes, and progressive question sets that motivate students to internalize and apply what they've learned.s
Keywords: Human anatomy; Human physiology